Oxide-Confined VCSEL with Enhanced Single-Mode Output Power Via two Oxide Layers with multiple apertures - Nazeri, Mohammad; Dinarvand, Ali (International Journal of Computer Sciences and Engineering, 2025)
A novel vertical-cavity surface emitting laser (VCSEL) based on two oxide layers with multiple apertures for the purpose of enlarging window aperture and maintaining single transverse mode operation is suggested and numerically investigated. The oxide layers with multiple aperture sizes structure has a number of advantages including easier fabrication in compare with multi-oxide layer structures, better mechanical stability, and very strong and high single-mode optical output power. The simulation results also show that this structure has a low threshold current. A comprehensive optical-electrical thermal-gain self-consistent VCSEL model is used to simulate and investigate the proposed structure. It has been shown that by using two oxide layers with multiple apertures in VCSEL, high single mode optical output power and a possibility of single-mode VCSEL with a large active area could be achieved.